Urban forests as refuges for terrestrial vertebrates: persistence and temporal activity in suburban Chennai, Southern India - Christudhas, Anulin; Narasimmarajan, Kannadasan; Jeswin, Stephen; Harikrishna, Prasanthan; Mathai, Manu Thomas (Nepalese Journal of Zoology, 2025)
Urban environments harbour many terrestrial vertebrate species. Apparently, urban forests are providing habitat for many terrestrial vertebrates without changing their spatial movement patterns, particularly without decreasing their home ranges in response to habitat limitation. Several species-specific studies suggest that urban vertebrates decrease their home ranges compared with non-urban counterparts; however, it remains unclear whether this pattern is widespread across taxa or restricted to specific taxonomic groups. Consequently, we conducted a camera trap survey in Madras Christian College Campus, Chennai, spanning approximately 317.45 acres (1.48 km²) of Southern Tropical Dry Evergreen Forests with high human pressure to study the persistence and temporal activity patterns of terrestrial vertebrates. Camera traps were deployed at 11 locations within the campus and detected nine species of terrestrial vertebrates between September 2021 and April 2022. The temporal activity pattern of the golden jackal and Indian crested porcupine was found to be nocturnal, the Indian Peafowl is crepuscular, and the Indian grey mongoose was found to be diurnal. The human movement pattern also appeared during midnight and midday. The golden jackal and jungle cat had >60% temporal activity overlap, the golden jackal and Indian crested porcupine had >40% overlap, the golden jackal and chital had >25%, and the Indian crested porcupine and Indian grey mongoose had